Study on batch cultures of gluconacetobacter dizaotrophicus using sucrose. - Molinari, Maria Laura (2013)
Background: Growth of Gluconacetobacter diazotrophicus with glucose as carbon an energy source has been extensively studied. But there are no reports in the literature describing growth of Gluconacetobacter diazotrophicus in batch culture containing sucrose as carbon source. The first step in sucrose pathway and production of levans was investigated. We focused in biomass, levans, gluconic acid and keto gluconic acids productions under different sucrose concentration and type nitrogen source. Results: The biomass production was maximal in culture containing 100 g/l sucrose and inorganic nitrogen. The gluconic acid was production in all condition, detecting up to 9 g/l in cultures with sucrose excess and biological N2-fixation. Keto gluconic acids were detectable only in cultures in sucrose excess and enriched with organic nitrogen sources. Levans production, although observed in all cultures, was maximal in batch culture with 100 g/l sucrose, BNF or organic nitrogen source with value was up to 25 g/l. It cultures were observed a significant LsdA expression. Conclusions: Ours results, not only describe some unknown aspect of G. diazotrophicus physiology, open the possibility of developed a technology of biomass, levans and gluconic acid production by G. diazotrophicus using sucrose as C-sources or an enzymatic extract. These products are interest biotechnology because they have a commercial important in different industrial process.